2014
DOI: 10.1093/toxsci/kfu173
|View full text |Cite
|
Sign up to set email alerts
|

Human Hepatocytes Support the Hypertrophic but not the Hyperplastic Response to the Murine Nongenotoxic Hepatocarcinogen Sodium Phenobarbital in an In Vivo Study Using a Chimeric Mouse with Humanized Liver

Abstract: High doses of sodium phenobarbital (NaPB), a constitutive androstane receptor (CAR) activator, have been shown to produce hepatocellular tumors in rodents by a mitogenic mode of action (MOA) involving CAR activation. The effect of 1-week dietary treatment with NaPB on liver weight and histopathology, hepatic CYP2B enzyme activity and CYP2B/3A mRNA expression, replicative DNA synthesis and selected genes related to cell proliferation, and functional transcriptomic and metabolomic analyses was studied in male CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
73
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 44 publications
7
73
1
Order By: Relevance
“…We have provided some experimental data showing a key species difference; those were that while PB stimulates replicative DNA synthesis in rodent hepatocytes, such proliferative effects are not observed in cultured human hepatocytes (Yamada et al, 2015;Hirose et al, 2009) nor in human hepatocytes of chimeric mice (Yamada et al, 2014). The lack of this key event in humans strongly supports the previous conclusion that the rodent carcinogenicity by CAR activators such as PB is not relevant to humans based on experimental and epidemiology data .…”
Section: Epsilon-momfluorothrinsupporting
confidence: 66%
See 4 more Smart Citations
“…We have provided some experimental data showing a key species difference; those were that while PB stimulates replicative DNA synthesis in rodent hepatocytes, such proliferative effects are not observed in cultured human hepatocytes (Yamada et al, 2015;Hirose et al, 2009) nor in human hepatocytes of chimeric mice (Yamada et al, 2014). The lack of this key event in humans strongly supports the previous conclusion that the rodent carcinogenicity by CAR activators such as PB is not relevant to humans based on experimental and epidemiology data .…”
Section: Epsilon-momfluorothrinsupporting
confidence: 66%
“…In keeping with the properties of the prototypic CAR activator PB, two closely structurally related pyrethroid insecticides metofluthrin (Yamada et al, 2015;Hirose et al, 2009) and momfluorothrin (present study) were demonstrated not to stimulate replicative DNA synthesis in cultured human hepatocytes. In addition, no stimulation of replicative DNA synthesis by NaPB in human hepatocytes has already been demonstrated in vivo in the study utilizing chimeric mice with human hepatocytes (Yamada et al, 2014). The present study demonstrated that momfluorothrin and metofluthrin did not increase in vivo human hepatocyte replicative DNA synthesis in chimeric mice employing hepatocytes from three different donors.…”
Section: Discussioncontrasting
confidence: 42%
See 3 more Smart Citations